Characterization of progressive HIV-associated tuberculosis using 2-deoxy-2-[(18)F]fluoro-D-glucose positron emission and computed tomography - Esmail, H; Lai, R; Lesosky, M; Wilkinson, K; Graham, C; Coussens, A; Oni, T; Warwick, J; Said-Hartley, Q; Koegelenberg, C; Walzl, G; Flynn, J; et al. (Nature Publishing Group, 2016)
Tuberculosis is classically divided into states of latent infection and active disease. Using combined positron emission and computed tomography in 35 asymptomatic, antiretroviral therapy naïve, HIV-1 infected adults with latent tuberculosis, we identified ten individuals with pulmonary abnormalities suggestive of subclinical, active disease who were significantly more likely to progress to clinical disease. Our findings challenge the conventional two-state paradigm and may aid future identification of biomarkers predictive of progression.